2007
DOI: 10.1007/s11243-007-0285-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and crystal structures of two cis/trans pyridine-cyclopalladated ferrocenylimine complexes

Abstract: Two new pyridine-cyclopalladated ferrocenylimine complexes (2a) and (2b) have been easily prepared from the reaction of halogen-bridged palladacyclic dimer (1a) and (1b) with pyridine in high yields. They were fully characterized by elemental analysis, M.s.-e.s.i., I.r., 1 H-n.m.r. and single-crystal X-ray analysis. Complex (2a) adopts a trans geometry in the solid state, while (2b) is cis. There are altogether four different types of intermolecular hydrogen bonds in their crystals. The impressing features inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The catalytic loadings could be lowered to 0.1 mol% without loss of activity (entry 7). Similar to the results for bromobenzene, good yields were also obtained in the case of 4-bromotoluene and 2-bromotoluene (entries [8][9]. Pd(dppf)Cl 2 [bis(diphenylphosphino)ferrocene] is a well known pre-catalyst that effectively catalyzes the reaction between 4-bromoacetophenone and phenyl boronic acid in toluene giving 94% yield [29].…”
Section: Application In Suzuki Coupling Reactionssupporting
confidence: 69%
See 1 more Smart Citation
“…The catalytic loadings could be lowered to 0.1 mol% without loss of activity (entry 7). Similar to the results for bromobenzene, good yields were also obtained in the case of 4-bromotoluene and 2-bromotoluene (entries [8][9]. Pd(dppf)Cl 2 [bis(diphenylphosphino)ferrocene] is a well known pre-catalyst that effectively catalyzes the reaction between 4-bromoacetophenone and phenyl boronic acid in toluene giving 94% yield [29].…”
Section: Application In Suzuki Coupling Reactionssupporting
confidence: 69%
“…For example, in palladium-catalyzed carbon-carbon bond formation reactions, palladacycles have shown superiority in many respects, due to their ready preparation and modification, high activity, and comparative stability [3][4][5][6]. In this respect, we have reported a variety of cyclometalated complexes containing N-donor ferrocenyl ligands and found that some cyclopalladated complexes are efficient catalysts for such coupling reactions [7][8][9][10][11][12]. In the cyclopalladation reactions of ferrocenylpyrimidines, owing to the poor solubility of the dimers, they were usually subjected to a bridge-splitting reaction with monophosphines to produce the corresponding monomers [10,12].…”
Section: Introductionmentioning
confidence: 99%